Eosinophilic infiltrates of the gastrointestinal tract. Issue 1 (January 1986) - Blackshaw, A J; Levison, D A
Abstract : There are two lesions which are often confused despite their quite distinct clinical and pathological differences: the inflammatory fibroid polyp and eosinophilic gastroenteritis. Other eosinophilic lesions likely to be encountered in the gut also pose problems of differential diagnosis.